Defect Engineering at Buried Interface of Perovskite Solar Cells - Mohamad Noh M.F.; Arzaee N.A.; Harif M.N.; Mat Teridi M.A.; Mohd Yusoff A.R.B.; Mahmood Zuhdi A.W. (John Wiley and Sons Inc, 2025)
Perovskite solar cells (PSC) have developed rapidly since the past decade with the aim to produce highly efficient photovoltaic technology at a low cost. Recently, physical and chemical defects at the buried interface of PSC including vacancies, impurities, lattice strain, and voids are identified as the next formidable hurdle to the further advancement of the performance of devices. The presence of these defects has unfavorably impacted many optoelectronic properties in the PSC, such as band alignment, charge extraction/recombination dynamics, ion migration behavior, and hydrophobicity. Herein, a broad but critical discussion on various essential aspects related to defects at the buried interface is provided. In particular, the defects existing at the surface of the underlying charge transporting layer (CTL) and the bottom surface of the perovskite film are initially elaborated. In situ and ex situ characterization approaches adopted to unveil hidden defects are elucidated to determine their influence on the efficiency, operational stability, and photocurrent?voltage hysteresis of PSC. A myriad of innovative strategies including defect management in CTL, the introduction of passivation materials, strain engineering, and morphological control used to address defects are also systematically elucidated to catalyze the further development of more efficient, reliable, and commercially viable photovoltaic devices. ? 2024 Wiley-VCH GmbH.